INSECTICIDE ACTION OF ETHANOL EXTRACTS OF SPONGES FROM URABÁ GULF ON Aedes aegypti AND Culex quinquefasciatus larvae - MARTÍNEZ M., Alejandro; GALEANO J., Elkin; CADAVID, Jorge; MIRANDA R., Yuly; LLANO L., Juliana; MONTALVO M., Karla (Vitae, 2009)
Due to increasing resistance of the vectors mosquitoes causing diseases of importance in public health, to chemical insecticides, is necessary the searching for alternative control methods, as the use of marine sponges extracts with insecticide activity, owing to its capacity of biodegradation and generation of minor environmental damage. In this work the insecticide activity is evaluated for the ethanol extracts of the marine sponges Amphimedon compressa, Topsentia ophiraphidites, Svenzea zeai, Ircinia campana. and Agelas. sventres, on stadium IV larvae of Aedes aegypti and Culex quinquefasciatus., in conditions of laboratory (25oC and 75 % Relative Humidity). The follow-up of the analysis is realized for evaluation and comparison of the percentage of mortality of each species at each extract concentration. The evaluated parameter is the response of the larvae to the effects of the ethanolic extracts of the sponges at three concentrations, 500, 200 and 100 ppm. Results demonstrates that Ircinia campana extract is most active against two insects, as long as the extract of Amphimedon compressa has a higher toxic effect on Aedes aegypti than on Culex quinquefasciatus.